Harnessing the collective intelligence of stakeholders for conservation. Issue 8 (30th June 2020) - Gray, Steven; Aminpour, Payam; Reza, Caitie; Scyphers, Steven; Grabowski, Jonathan; Murphy, Robert; Singer, Alison; Baltaxe, David; Jordan, Rebecca; Jetter, Antonie; Introne, Joshua
Abstract : Incorporating relevant stakeholder input into conservation decision making is fundamentally challenging yet critical for understanding both the status of, and human pressures on, natural resources. Collective intelligence (CI), defined as the ability of a group to accomplish difficult tasks more effectively than individuals, is a growing area of investigation, with implications for improving ecological decision making. However, many questions remain about the ways in which emerging internet technologies can be used to apply CI to natural resource management. We examined how synchronous social‐swarming technologies and asynchronous "wisdom of crowds" techniques can be used as potential conservation tools for estimating the status of natural resources exploited by humans. Using an example from a recreational fishery, we show that the CI of a group of anglers can be harnessed through cyber‐enabled technologies. We demonstrate how such approaches – as compared against empirical data – could provide surprisingly accurate estimates that align with formal scientific estimates. Finally, we offer a practical approach for using resource stakeholders to assist in managing ecosystems, especially in data‐poor situations.